The Ethical Case against Animal Experiments - Linzey, Clair; Linzey, Andrew (Book collections on Project MUSE., 2018)
"At present, human beings worldwide are using an estimated 115.3 million animals in experiments--a normalization of the unthinkable on an immense scale. In terms of harm, pain, suffering, and death, animal experiments constitute one of the major moral issues of our time. Given today's deeper understanding of animal sentience, the contributors to this volume argue that we must afford animals a special moral consideration that precludes their use in experiments. The Ethical Case against Animal Experiments begins with the Oxford Centre for Animal Ethics's groundbreaking and comprehensive ethical critique of the practice of animal experiments. A second section offers original writings that engage with, and elaborate on, aspects of the Oxford Centre report. The essayists explore historical, philosophical, and personal perspectives that range from animal experiments in classical times to the place of necessity in animal research to one researcher's painful journey from researcher to opponent. A devastating look at a contemporary moral crisis, The Ethical Case against Animal Experiments melds logic and compassion to mount a powerful challenge to human cruelty" --